Un espace alternatif du politique ? Les souscriptions au profit d’exilés étrangers accueillis en France, années 1820-1840 - Delphine Diaz (Mélanges de la Casa de Velázquez, 2022)
This study focuses on the forms of mobilization of civil society for the benefit of exiles and refugees welcomed in France under the Restoration and the July Monarchy. The article analyses the subscriptions organised in favour of the Greeks in the 1820s, then in favour of the Spaniards, Italians and above all the Poles from the 1830s onwards, by studying the example of the subscriptions opened in the town of Chalon-sur-Saône in 1832. Why did some French people decide to commit themselves to the cause of foreigners in exile, and what meaning could this gesture have, in a local, national or international political context? How did French donors organise their donations materially, and what type of expenditure did they finance? We will examine the subscribers who committed funds to support refugees, with a particular focus on two categories of individuals who were excluded from exercising the right to vote in France at the time: women and members of the working classes.